Le rose et le bleu : la fabrique du féminin et du masculin - Beauvalet-Boutouyrie, Scarlett; Berthiaud, Emmanuelle (Collection Histoire (Paris. 2013), 2016)
Une histoire de l'étude biologique, des statuts, des droits, de l'éducation, des apparences et des rôles attendus des hommes et des femmes, du XVIe au XXIe siècle, qui interroge la fabrication des concepts de masculin et de féminin.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; approches et analyses; cours; discipline; histoire; histoire et politique; postmodernisme; premier cycle; psy4910; psychologie; périodes historiques; sciences humaines; sexe/genre; stéréotypes de genre; thématiques; études de genres

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Lesbian camp: An unearthing - Nielsen, Elly-Jean (Journal of Lesbian Studies, 2016)
Camp—a sensibility, a style, and a form of artistic selfexpression—is an elusive concept said to be in the eye of the beholder. To refute Susan Sontag’s (1966) claims that camp is apolitical and not especially homosexual, a number of recent scholarly works have been geared toward revealing camp’s fundamental gayness. With the odd footnote aside, lesbian camp has been collapsed into the category of gay male camp, if not eclipsed entirely. Despite the negligible efforts made to legitimize lesbian camp, there are numerous salient cultural examples one might draw on to illustrate, typify, and substantiate a lesbian camp sensibility. I lay the ground work for this scholarly exercise by outlining various definitions and critiques of camp, and by discussing its history and application to queer theory. Then, to unveil lesbian camp, three nonmutually exclusive categories are discussed: classic, erotic, and radical. By gathering various strands of inquiry, and various textual examples (e.g., photography, artistic performances, and literary tropes), this article attempts to reach a more inclusive and nuanced understanding of lesbian camp.
Keywords: approches et analyses; butch/femme; discipline; personnes lesbiennes; psychologie; queer; ressource en ligne; sciences humaines

Genre et psychanalyse : la différence des sexes en question - Rassial, Jean-Jacques; Chevalier, Fanny; Colloque Genre et psychanalyse (Érès poche, 2016)
« La remise en cause de l’évidence naturelle jusque-là accordée à la différence des sexes occupe la scène des débats publics et se retrouve théorisée par l’émergence du concept de « genre » dans sa distinction d’avec le sexe. La différenciation entre sexe et genre émerge d’une fracture avec l’idée que le sexe biologique déterminerait l’identité sexuée et sexuelle. Dans cette nouvelle terminologie, le sexe ne renvoie plus alors qu’à la dimension anatomique et biologique tandis que le genre réfère à la construction psychologique et sociale du sexe. Malgré la pluralité des théories auxquelles le genre a donné naissance, l’émergence de cette notion prend en compte que sexe anatomique, sexuation psychique et sexualité peuvent trouver des nouages autres que ceux promus par des normes confondues avec l’ordre naturel – nouage, souligne la psychanalyse, radicalement singulier pour chacun. Cet ouvrage propose une introduction à toute la complexité de ces questions. Il axe son propos sur les controverses entre les théories psychanalytiques et les études sur le genre, et ouvre le dialogue à la littérature, à la philosophie et au cinéma. Cette perspective pluridisciplinaire reflète ainsi l’hétérogénéité des différents abords et usages du genre. »-- Résumé de l'éditeur.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; cours; discipline; genre; identité sexuelle; identités LGBTQIA2+; post-structuralisme; premier cycle; psy4910; psychanalyse; psychologie; périodes historiques; ressource en ligne; sciences; sciences humaines; sexe/genre; thématiques